On history, business, and management: a review of the literature and research agenda - da Silva, Ítalo; Santos, Elisabeth Cavalcante dos (Revista de Administração da UFSM, 2022)
Purpose – The purpose of this article is to conduct a systematic review of the literature on business history and management history in specialized journals in the area. Design/methodology/approach – We conducted a systematic review of the literature in the journals: Business History, Business History Review, Journal of Management History, and Management & Organizational History, between 2011 and 2020. In all, we analyzed 231 articles using the open, axial coding technique, and selective. Findings – We answered two central analytical questions about the researchers' theoretical-methodological choices and summarized the results in six research lines. Historiographic approaches are presented from the epistemologies, theories, methods, contributions, limitations, and research problems chosen by the researchers in their articles. Originality/value (mandatory) – The article is contributory when it assumes the central premise that the understanding of the researchers' theoretical-methodological decisions results in the historiographic approaches adopted in business and management research. Also, we offer a research agenda concerned with problems about (1) marginal empirical contexts, (2) the comparative approach to history; and (3) the perception of the past as a historical narrative.